Ricardo Palma and the English language - Zegarra del Castillo, Claudia Isabel (2019)
Following the spirit of reflection of the patriarch of letters, this presentation aims to show certain aspects of Ricardo Palma’s life as a translator and expert on the work of the most representative literary figures of European and American Romanticism. Several authors and numerous sources show Palma’s first contact with outstanding English-speaking writers, who are believed to have encouraged the writer to dedicate many hours stolen from his free time to translating, producing his own verses and perfecting the literary style with which he would consecrate the great intellectual evolution of his works. It is the translator’s duty to explore the biography of every writer to discover the hidden messages between his pen and his pages, as knowing the close relationship that Palma maintained over the years with English culture could bring us closer to the true spirit of his passion for literature.